(untitled) (Journal of the College of Basic Education, 2022)
The strength of any country has three elements: economy, health and science. Therefore, the colonial countries are trying to destroy the economy and spread poverty, destroy health institutions to spread disease, and destroy scientific centers and scientists to spread ignorance and underdevelopment and the causes of weakness of countries is (poverty, disease and underdevelopment) so many countries sought to destroy the foundations of power in Iraq . Including centers, scientific institutions and scientists, through murder, kidnapping and displacement. Then emigrated from Iraq the best scientific Competencies of various disciplines. The aim of this research is to identify (the role of television programs in reducing phenomenon of migration phenomenon), and a sample of drama and news programs has been selected from a number of media organizations from twin Iraqi satellite channels, Al-Iraqiya and Al-Sharqiya. Within researching the drama programs that dealt with migration. The researchers did not get any dramatic work on this subject AL- Iraqia channel. Al - Sharqiya channel has produced a single series (phobia of Baghdad) and has been analyzed according to the search’s tool of the selected frame indicators. Has been modified and approved by a group of experts, and the study produced many of important results: 1 - Most satellite TV channels did not deal the migration, only one series, only some news. 2 - The absence of development programs that contribute to the promotion of science and scientists as a national wealth. 3 - TV programs did not provide solutions and proposals to solve the problem of migration and did not identify the parties that stand behind it. 4 - Some of the television programs imported gave idea about stability and Welfare living in America and Europe, which prompted many people to seek to migrate to those countries The search has been completed with a list of sources and references.